Property Rights in Kaiapoi - Tau, Te Maire (Victoria University of Wellington Law Review, 2016)
Māori property rights have been a much discussed topic over the years, but often under false assumptions and pretences. Traditionally accepted views highlight the communal nature of Māori property rights prior to European contact. It is now assumed that individual rights or property rights were a Western construct imposed on Māori, who it is believed held land in common. This article argues that there was no contradiction in the idea of a tribe holding its territory as a collective while also having individual ownership of land and resources. At the same time we need to be careful of over-extending western notions of property to Māori or any other non-western peoples, an outcome of the colonial narrative. This article attempts to remove the idea that property rights among Māori were communal and that individual title rights did not exist. It will do this by looking at the "Kaiapoi Experiment" of 1859.